Waqf Pledge Deed Official (PPAIW) Based on Waqf Law, the Notary - Gloria Gita Putri Ginting (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The ratification of the nazhir legal entity is related to the Notary's role in the waqf legal actions that have been ongoing thus far. The purpose of this research is to ascertain the Authority of a Notary to act as the Official for Making Waqf Pledges (PPAIW) and the implementation of the making of the Waqf Pledge Deed by a Notary who acts as the Official for Making Waqf Pledges (PPAIW). This examination is a clear exploration. Enlightening exploration expects to precisely depict the qualities of an individual, condition, side effect or certain gathering, or to decide the spread of a side effect, or to decide if there is a connection among side effects and different side effects in the public eye. Execution of making the Deed of Waqf Promise completed by a Legal official as PPAIW which is as expressed in the clarification of the arrangements of the Law on Legal official Position Number 2 of 2014 concerning Revisions to Regulation Number 30 of 2004 concerning.